Teacher malaise, suffering and sickness: from narratives of teacher work and culture to teaching as a profession - Penteado, Regina Zanella [UNESP]; Neto, Samuel de Souza [UNESP] (Univ Sao Paulo, Fac Saude Publica, 2019)
This study aims to present a critical analysis of teacher malaise, suffering and sickness related to the history of the teaching work, the ways of acting in this occupation, and the culture of teaching. The methodology involved a narrative literature review of 12 selected publications to identify the main aspects attributed to epidemiological issues, naturalization of the problem in teaching, public policies, teaching work organization and professional identity. The discussion seeks to highlight the forms of visibility and invisibility of this issue in the social and educational scenario in Brazil, with a focus on teacher work and training and the culture of teaching based on insights of Maurice Tardif regarding the 'ages of teaching'. This study shows how teacher malaise, suffering and sickness can express collective narratives of teachers characterized by vocation and professional socialization through feminization - and how social, historical and cultural dimensions of teaching work can affect the collective ways to perceive and take care of the body and health, and cause sickness. Finally, it highlights the challenge to consider body/health/well-being in the culture of teaching as elements that support professional development and the professionalization of teaching profession.
Keywords: Education; Collective Health; Teaching Work; Teacher Training; Teaching Professionalization of Teaching Profession